Cytotoxicity Test of Ethanol Extract of Herb Sintrong (Crassocephalum crepidioides (Benth.) S. Moore) Against Artemia Salina Leach Shrimp Larvae Using the BSLT Method - Tambupolon, Sanya Tanika; Ridwanto, Ridwanto (Pustaka Media Publishing, 2023)
Cancer is a disease that arises as a result of an error in the division system at the cell level resulting in abnormal cell growth with a continuous, uncontrolled growth rate that can change shape and spread to other organs or is called metastasis. One of the plants that has the potential as an anticancer is the herb sintrong (Crassocephalum crepidiodes (Benth.) S. Moore). The purpose of this study was to determine the class of secondary metabolites contained in the powder and ethanol extract of the herb sintrong (Crassocephalum crepidioides (benth.) S. Moore) and its cytotoxicity by looking at the LC50 value using the Brine Shrimp Lethality Test (BSLT) method.Cytotoxicity testing was carried out using the BSLT method with Artemia salina Leach shrimp larvae as test animals with concentrations of 100-1000 µg/mL, with negative control without added extract. The LC50 value was analyzed using a straight line regression equation by entering data on the probit value and the logarithm of the concentration.The secondary metabolite compounds contained in sintrong herb (Crassocephalum crepidiodes (Benth.) S. Moore) using the phytochemical screening method are flavonoids, alkaloids, tannins, saponins and steroids. Based on the results of the toxicity test using the Brine Shrimp Lethality Test (BSLT) method, the LC50 value = 295.3800 µg/mL showed that the sintrong herb extract is toxic and has the potential as an anticancer. The test compound is said to be toxic if the LC50 value is ˂1000 µg/mL.